PENGARUH KEPUASAN PENGGUNA SISTEM INTEGRASI ONLINE TERHADAP KINERJA INDIVIDU (Studi Kasus pada Perusahaan Konsultan IT PT X di Jawa Timur) - Alvitasari, Geby Nidia (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study, which adopts the Information System Success Model of DeLone and McLean (2003), aims to empirically identify the relationship between system quality, information quality, and service quality with the users’ satisfaction, as well as to analyze the influence of such satisfaction upon the individual performance. The data are collected from 72 respondents working at PT. X, which uses Online Integration System (SIO), and analyzed using PLS as part of SEM. The result of the study shows that system quality, information quality, and service quality have a positive relationship and a significant effect on users’ satisfaction, and such satisfaction significantly influences the individual performance. The individual performance, in turn, supports perceived productivity, followed by the increase of decision making quality. This conclusive scheme may be used by the company as a basis for future improvement of better quality SIO. Keywords: System Quality; Information Quality; Service Quality; Users’ Satisfaction; Individual Performance